Systolic blood pressure and outcome in patients admitted with acute heart failure: a pooled analysis from 4 randomized clinical trials. (26th April 2021) - Grand, J; Miger, K; Sajadieh, A; Kober, L; Torp-Pedersen, C; Ertl, G; Sendon, JL; Maggioni, AP; W Nielsen, O
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): The Danish Heart Foundation Background: In acute heart failure (AHF), low systolic blood pressure (SBP) has been associated with poor outcome. Less is known of the risk related to normal versus elevated SBP and interaction with left ventricular ejection fraction. Purpose: The aim of the present study was to assess the association between baseline SBP and short- and long-term outcome in a large cohort of AHF-patients. Methods: A pooled cohort of four randomized controlled trials investigating the vasodilator serelaxin versus placebo in patients admitted with AHF and an SBP from 125 to 180 mmHg. Endpoints were 180-day all-cause mortality and a short-term composite endpoint (worsening heart failure, all-cause mortality or hospital readmission for HF through Day 14). Left ventricular ejection fraction (LVEF) was categorized into HFrEF (<40%) and HFpEF (= >40%). Multivariable Cox regression was used and adjusted for age, sex, baseline body mass index, HFrEF, serum estimated glomerular filtration rate, allocated treatment (placebo/serelaxin), diabetes mellitus, ischemic heart disease, and atrial fibrillation/flutter. Measurements and Main Results: A total of 10.533 patients with a mean age of 73 (±12) years and median SBP of 140 (130-150) mmHg were included within mean 8.2 hours from admission. LVEF was assessed in 8493 (81%), and of these, 4294 (51%) had HFrEF. Increasing SBP as a continuous variable was inversely associated with 180-day mortality (HRadjusted: 0.93 [0.88-0.98], p = 0.004 per 10 mmHg increase) and with the composite endpoint (HRadjusted: 0.90 [0.85-0.95], p < 0.0001 per 10 mmHg increase). A significant interaction was observed regarding LVEF, revealing that SBP was not associated with mortality in patients with HFpEF (HRadjusted: 1.01 [0.94-1.09], p = 0.83 per 10 mmHg increase), but SBP was associated with increased mortality in HFrEF (HRadjusted: 0.80 [0.73-0.88], p < 0.001 per 10 mmHg increase) (Figure). Conclusions: Elevated SBP is independently associated with favorable short- and long-term outcome in AHF-patients. The association between SBP and mortality was, however, not present in patients with preserved LVEF.